2020
DOI: 10.1051/0004-6361/202038363
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hydrodynamic simulations of the upper atmosphere of π Men c: Comparison with Lyα transit observations

Abstract: Context. π Men c is the first planet to have been discovered by the Transiting Exoplanet Survey Satellite. It orbits a bright, nearby star and has a relatively low average density, making it an excellent target for atmospheric characterisation. The existing planetary upper atmosphere models of π Men c predict significant atmospheric escape, but Lyα transit observations indicate the non-detection of hydrogen escaping from the planet. Aims. Our study is aimed at constraining the conditions of the wind and high-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Unlike the case for π Men c, there is strong evidence that these other exoplanets' atmospheres are H 2 /He-dominated. The transit depth and Doppler velocities reported here are consistent with the C II ions being swept by the stellar wind into a ∼15 R p wide (about the extent of the Roche lobe in the substellar direction, and closer to the planet than the interface between the planetary and stellar winds) tail and accelerated to high velocities, a scenario suggested by 3D models of π Men c and other exoplanets (Shaikhislamov et al 2020a(Shaikhislamov et al , 2020b. We found by means of a simplified phenomenological model of π Men cʼs tail (Appendix B) that the C II measurements can be explained if the planet loses carbon at a rate 10 8 g s −1 , requiring that the atmosphere contains this atom in at least solar abundance.…”
Section: Observationssupporting
confidence: 84%
See 3 more Smart Citations
“…Unlike the case for π Men c, there is strong evidence that these other exoplanets' atmospheres are H 2 /He-dominated. The transit depth and Doppler velocities reported here are consistent with the C II ions being swept by the stellar wind into a ∼15 R p wide (about the extent of the Roche lobe in the substellar direction, and closer to the planet than the interface between the planetary and stellar winds) tail and accelerated to high velocities, a scenario suggested by 3D models of π Men c and other exoplanets (Shaikhislamov et al 2020a(Shaikhislamov et al , 2020b. We found by means of a simplified phenomenological model of π Men cʼs tail (Appendix B) that the C II measurements can be explained if the planet loses carbon at a rate 10 8 g s −1 , requiring that the atmosphere contains this atom in at least solar abundance.…”
Section: Observationssupporting
confidence: 84%
“…The spectroscopic velocity of +10 km s −1 for the C II ions is consistent with our photochemical-hydrodynamic predictions, and likely traces absorption in the vicinity of the planet's dayside as the gas accelerates toward the star. Comparable velocities are predicted by 3D models on the planet's dayside (Shaikhislamov et al 2020a) before the escaping gas interacts with the impinging stellar wind. Negative velocities of −70 km s −1 (and probably faster, as the stellar line becomes weak and the S/N poor at the corresponding wavelengths) suggest that the C II ions are accelerated away from the star by other mechanisms such as tidal forces and magnetohydrodynamic interactions with the stellar wind.…”
Section: Appendix B Phenomenological Model Of the Ion Tailmentioning
confidence: 86%
See 2 more Smart Citations
“…The most important characteristic -the mass-loss rate -is equal to about 3 × 10 9 g/s in Loyd et al (2017) and 3.3 × 10 9 g/s in the 3D calculation. Thus, for the first time, 3D simulations have indicated that the main quantitative parameters of atmospheric escape from highly irradiated exoplanets can be accurately simulated by 1D models (see also Shaikhislamov et al 2020, for the case of the super-Earth π Men c). This is because the outflow is driven mostly in the upper atmosphere and because the day-side heating by XUV is efficiently redistributed over the whole atmosphere by zonal flows.…”
Section: Towards Sophisticated Mass-loss Modelsmentioning
confidence: 91%